Inventing the Perfect Crush: Arguing for Middle-Grade Narratives with Aromantic Leads - Varsha Varghese (Leaf Journal)
In this article, I set out some of the concerns and issues I faced while planning and writing a middle-grade novel. The novel, Ash's Infallible Guide for the Perfect Crush, set in an Indian middle school, stars an aromantic protagonist. I argue that, while Young Adult (YA) fiction is seeing an increase in the number of asexual and aromantic characters as part of a wider increase in LGBTQA+ fiction, these portrayals tend to be of white or American characters. Often they are ‘out’ when the story begins. This meant that these YA counterparts couldn’t serve as exemplars for my own work-in-progress. Other compounding difficulties were the issues of when someone might know they are aromantic or asexual (limited studies suggest that these identities are somewhat less stable than other minority sexualities), and the more conservative nature of Indian children’s publishing. These issues have all affected my decision-making as an author and the personality of Ash, at the heart of the novel.